PREVALENCE AND CORRELATION WITH CLINICO RADIOLOGICAL FEATURES OF PARKINSON’S DISEASE WITH AUTONOMIC DYSFUNCTION - Dr Manoj Kumar Katragadda; Dr Ch Sushma; Dr T Sateesh Kumar; Dr S Gopi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Autonomic dysfunction occurs not only in advanced PD but also early in its course. Transcranial ultrasound can pick up SN abnormalities very early in the disease. There are no Indian studies which correlated autonomic dysfunction with TCUS findings. Objectives: This study aims to study prevalence of autonomic dysfunction, to correlate with clinico-imageological features and to assess the impact of autonomic dysfunction on quality of life. Materials and methods: This is a Retrospective and Prospective study, with 45 PD patients taken from Movement clinic, NIMS, Hyderabad from Jan 2016-June 2017.PD diagnosis based on UKPD society Brain Bank Criteria, For motor evaluation –1)H&Y staging2)UPDRSIII on off staging, Questionnaires used were 1.SCOPA–AUT,2.PDQ 39,3.MOCA&Lab Tests:1.Autonomic Function Tests,2.Transcranialultrasound. Results: Out of 45 patients males were 34 and females were 11. The mean UPDRS III Off Score and On Score were 47.7±14.6 and 15.4±7.7 respectively. The mean H and Y score was 2.1.The PDQ-39SS and SCOPA- AUTSS were 57.6±34.6 (0-120) and 6.33 ±5.4(0-23)respectively. The Parasympathetic and Sympathetic dysfunction found in 53% (N-24) and 31% (N-19) respectively. 24(53%) had tremor and 21(47%) had rigidity predominance. The parasympathetic and sympathetic dysfunction on AFT were more in tremor patients compared to rigidity patients (p value-0.001for parasympathetic and 0.003 for sympathetic dysfunction. Significant Laterality index was found in 38 (84.44%). Conclusions: Most common self-reported autonomic symptoms were constipation and postural dizziness. AFT showed significant autonomic dysfunction even in those who had no autonomic symptoms .Based on our and previous studies we recommend objective autonomic function evaluation in every patient of IPD.SN hyperintensity didn’t correlated with autonomic dysfunction.PDQ39sum Score was higher in those with autonomic dysfunction affecting quality of life.